Analysis of the public HARPS/ESO spectroscopic archive: Ca II H&K time series for the HARPS radial velocity database - Perdelwitz, Volker; Trifonov, Trifon; Teklu, J. T.; Sreenivas, K. R.; Tal-Or, L. (Astronomy and astrophysics, 2024)
Context. Magnetic activity is currently the primary limiting factor in radial velocity (RV) exoplanet searches. Even inactive stars, such as the Sun, exhibit RV jitter of the order of a few m s−1 due to active regions on their surfaces. Time series of chromospheric activity indicators, such as the Ca II H&K lines, can be utilized to reduce the impact of such activity phenomena on exoplanet search programmes. In addition, the identification and correction of instrumental effects can improve the precision of RV exoplanet surveys. Aims. We aim to update the HARPS -RVBANK RV database and include an additional 3.5 yr of time series and Ca II H&K lines (RHK) chromospheric activity indicators. This additional data will aid in the analysis of the impact of stellar magnetic activity on the RV time series obtained with the HARPS instrument. Our updated database aims to provide a valuable resource for the exoplanet community in understanding and mitigating the effects of such stellar magnetic activity on RV measurements. Methods. The new HARPS-RVBANK database includes all stellar spectra obtained with the HARPS instrument prior to January 2022. The RVs corrected for small but significant nightly zero-point variations were calculated using an established method. The R′HK estimates were determined from both individual spectra and co-added template spectra with the use of model atmospheres. As input for our derivation of R′HK, we derived stellar parameters from co-added, high signal-to-noise ratio templates for a total of 3230 stars using the stellar parameter code SPECIES. Results. The new version of the HARPS RV database has a total of 252 615 RVs of 5239 stars. Of these, 195 387 have R′HK values, which corresponds to 77% of all publicly available HARPS spectra. Currently, this is the largest public database of high-precision (down to ~1 m s−1) RVs, and the largest compilation of R′HK measurements. We also derived lower limits for the RV jitter of F-, G-, and K-type stars as a function of R′HK.